An atypical presentation of malaria in a 19-year-old woman. (2022) - Malhotra, Radhika; Manoharan, Anjella; Nyaku, Amesika N.; Castro, Dorothy
Abstract: We describe an atypical presentation of malaria in a 19-year-old female who emigrated from Nigeria to the United States one year prior to presentation. Her primary complaint was fever and occipital headache radiating down to the neck. Rapid antigen testing was positive for Plasmodium vivax/ovale and microscopy demonstrated the same. She received treatment with atovaquone-proguanil with improvement in symptoms but was lost to outpatient follow up. This case is unusual in several aspects: the 12-month latency in disease manifestation after her last epidemiologic exposure and the recovery of P. vivax/ovale which is uncommon in Nigeria. Appropriate identification of travel history, clinical presentation and disease epidemiology are necessary to guide pharmacologic treatment.